ANALYSIS OF CARE TO THE MOTHER-BABY BINOMIAL IN A CENTER FOR NORMAL DELIVERY - Flávia Ribeiro Rocha; Manuela Costa Melo; Gerusa Amaral de Medeiros; Érica Possidônea Pereira; Lara Mabelle Milfont Boeckmann; Luz Marina Alfonso Dutra (Universidade Federal do Paraná, 2017)
The present study aimed to gain insight on care to the mother-baby binomial in a Center for Normal Delivery of Brazil's public health network, for women who had previous deliveries in the hospital network. Descriptive qualitative study with eight women resident in Brasilia who had just given birth, through semi-structured interviews. Data was collected between February and July 2015. For data treatment, content analysis in thematic modality was used. Three categories emerged: "Good Delivery and Birth Care Practices and Parturients' Autonomy in the Decision-making Process", "Care versus Neglect" and "Indifference to the Suffering of Others". The Center for Normal Delivery implemented good delivery and birth care practices, and the participants were satisfied with the care provided to them. The study showed the women's empowerment to become more involved and informed on the process of giving birth and on their rights and stresses the need for the establishment of more Normal Birth Centers in the country to ensure good birth care practices.